Susceptibility to Phytophthora cinnamomi of the commonest morphotypes of Holm oak in southern Spain (Forest Pathology, 2012)
The four main morphotypes of Holm oak (Quercus ilex subsp. ballota) present in Andalusia (expansa, macrocarpa, microcarpa and rotundifolia) were infected with Phytophthora cinnamomi to determine their susceptibility to the root pathogen. No large differences were found among the four morphotypes in the infection of roots, which always showed a high degree of necrosis. However, the different responses of the foliage to infection separated the four morphotypes of Holm oak into three groups: very susceptible (microcarpa), susceptible (expansa) and moderately susceptible (rotundifolia and macrocarpa). The natural hybrid Q. ilex ballota–Q. faginea exhibited a low level of root and foliar symptoms when infected with P. cinnamomi. Quercus faginea could be considered as a source of resistance to P. cinnamomi in future breeding programmes.

The role of yellow lupin (Lupinus luteus) in the decline affecting oak agroforestry ecosystems (Forest Pathology, 2011)
Phytophthora cinnamomi is a soilborne pathogen causing root rot in Mediterranean Quercus species growing in dehesa rangeland ecosystems. Recently, it has been reported causing wilting and death of Lupinus luteus (yellow lupin), a spontaneous plant in southern Spain rangelands, but also frequently sowed for livestock grazing. In soils artiﬁcially infested with P. cinnamomi chlamydospores and planted with diﬀerent cultivars of yellow lupin, a signiﬁcant increase in the density of propagules was detected in comparison with the initial levels of inoculum and with the infested but not planted soil (control). In oak-rangelands in which yellow lupine was planted, isolation and counting of colonies of P. cinnamomi from soil samples have shown the ability of this plant to maintain or even increase the inoculum density and thus facilitate the infection of trees. Results suggested that cultivation of yellow lupin in oak-rangeland ecosystems should be avoided whether oak trees are aﬀected by root disease caused by P. cinnamomi or not. This leguminous plant can act as an inoculum reservoir or even enhance inoculum soil levels available for oak root infections, exacerbating the oak decline severity in the region.

INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.

La productividad de bellota en la dehesa y su relación con parámetros meteorológicos (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Economically, holm-oak acorn crop is the major component in Iberian Mediterranean eco- systems. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years, because of variables as masting, weather, etc. From 2001 to 2006 we studied fruit production and meteorology in a holm-oak natural area of South Spain. The results obtained, indicated that weather conditions at spring and autumn beginning had a marked influence on acorn production. Flowering survival and production improved by mild temperature in March and crop acorn was stronger because of rainfall in September